(3GdJMcje aj efGRYGJ GdYbhO GdGOGQjI GdOGNdjI hGdOhdjI (B/s - (3NdjaI, YHO GdYRjR YHO GdefYes ((3GdGScfOQjI(B: s (3OGQ GdacQ GdLGeYj(B, s, 2006)
(3eGgjI GdJMcje hGLQGAGJg(B, (3eGgjI GdYbO GdGOGQj GdOGNdj(B, (3ehba Gdabg h GdbVGA ef GdJMcje aj GdYbhO GdGOGQjI GdOGNdjI bHd UOhQ GdbGfhf Qbe (B27 (3SfI (B1994(3h cPG ehba GdeTQY ef GdJMcje aj GdYbhO GdGOGQjI GVGaI Gdi eaghe GdYbO GdGOGQj GdOhdj h eHQQGJ GdJMcje aj efGRYGJg h GdJMcje aj GdGJaGbjGJ GdOhdjI(B, (3JWHjbGJ YedjI GdJMcje aj HYV GdYbhO GdGOGQjI GdOhdjI(B.s
(3eQGLY U(B.165s
Keywords: (3GdJMcje(B, (3GdYbhO GdGOGQjIs; (3GdefGRYGJ GdOhdjIs